LOW-COST ALTERNATIVE BUILDING MATERIALS MADE WITH RECYCLED MORTAR (International Journal of Food and Nutritional Sciences, 2023)
ABSTRACTRapid development of technology and lifestyle has led to increased use of industrial products and that in turn producing a huge amount of waste. Also, in the present situation world in leaning towards the overall infrastructural development so, this has created demanding conditions for in two opposite directions. One being the demand for the raw materials for the construction caused by the increased infrastructural development and the other being the demand for disposal of waste due to increased amount of industrial product usage. To achieve both demands simultaneously one must look for the ways to use the waste materials in construction process as substitute for conventional raw materials. Considering these present time problems of industrial waste management and increasing cost of construction, this paper focuses on the production of building blocks with sufficient strength at a reduced cost. In this work, replacement of conventional raw materials of construction i.e., cement by lime and sand by waste materials such as stone fines and stone dust is done and strength and cost analysis are carried out by comparing with the cost of conventional blocks made by using standard cement and sand.